OUTCOME OF MONKEYPOX INFECTION IN GRAVIDA: A LITERATURE REVIEW - Salsabila Rahma Nurani Putri; James Kevin Alfedo; Reny I'tishom (Universitas Airlangga, 2023)
Monkeypox is a smallpox-like disease which is an important globally emerging infectious disease caused by the monkeypox virus. WHO declared monkeypox a public health emergency on 23 July 2022. Most research on monkeypox infection in humans has not included pregnant people. However, previous studies in pregnancy on the outcome of infection with smallpox viruses belonging to the Poxviridae family have reported high mortality rates. This literature review aims to determine the effects of monkey pox on pregnancy. Methods: Writing literature reviews is done by searching the Pubmed, Sciencedirect, Web of Science, and Scopus databases. A literature search was carried out using the keywords "outcome", "monkeypox", and "pregnancy". Searches using these keywords are limited to 2014 - 2023 (the last 10 years) and then screening according to inclusion and exclusion criteria. Results: A total of three included literature were reviewed using a qualitative descriptive method. The three literatures reinforce each other by finding signs and symptoms of monkeypox in neonates, besides that there are also pregnant women who experience miscarriages. However, there is one literature which states that there is no monkeypox transmission from pregnant women with monkeypox to neonates. Conclusion: The findings from this literature review indicate that the impact of monkeypox on pregnancy is closely associated with a high risk of miscarriage, intrauterine fetal death, vertical transmission, and complaints in pregnant women due to monkeypox infection. Health workers are advised to be more alert to monkeypox cases in pregnancy due to the relatively high risk of fetal death in pregnant women in endemic areas and during monkeypox epidemics.